Super Edge Connectivity Number of an Arithmetic Graph - S. Sujitha; Mary Jenitha Lazer (Journal of the Indonesian Mathematical Society, 2022)
An edge subset F of a connected graph G is a super edge cut if G − F is disconnected and every component of G−F has atleast two vertices. The minimum cardinality of super edge cut is called super edge connectivity number and it is denoted by λ'(G). Every arithmetic graph G = Vn, n not equal to p1 × p2 has super edge cut. In this paper, the authors study super edge connectivity number of an arithmetic graphs G = Vn, n = p_1^a_1 × p_2^a_2 ,  a1 > 1, a2 ≥ 1, and G = Vn, n = p_1^a_1 × p_2^a_2 × · · · ×p_r^a_r , r > 2, ai ≥ 1, 1 ≤ i ≤ r.